Study on the types of abuse in young couples as a function of sex - González-Gijón, Gracia; Jiménez-Rios, Francisco Javier; Martínez-Heredia, Nazaret; Soriano Díaz, Andrés (Frontiers in Psychology, 2023)
This study analyses the types of violence that can occur in young people's intimate relationships among young people and their self-perception of abuse. We have used a survey-type methodology, with a quantitative approach. The participants were selected by means of a non-probabilistic convenience sampling among students by convenience, students of different Degrees and Postgraduate courses in the Faculty of Education Sciences of the University of Granada (Spain). The sample consisted of 323 students, with a mean age of 23.8 years (SD=5.2). The data, statistical and inferential tests were carried out with the data obtained using the data analysis programme SPSS V26 data analysis programme. The results obtained show that the type of mal-treatment most suffered, at some time by the participating sample, is emotional maltreatment, physical maltreatment and physical abuse, emotional, physical and psychological abuse. By comparing the means obtained according to gender, we can conclude that gender does not influence the violence suffered by young couples, which gives it a bidirectional character.This study analyses the types of violence that can occur in intimate partner relationships among young people and their self-perception of abuse. For this purpose, we have used a survey-type methodology, with a quantitative approach. Participants were selected by means of non-probabilistic convenience, students of different Degrees and Postgraduate courses in the Faculty of Education Sciences of the University of Granada (Spain) The sample consisted of 323 students, with a mean age of 23.8 years (SD=5.2). Statistical and inferential tests were carried out with the data obtained using the SPSS V26 data analysis programme. The results obtained show that the type of maltreatment most suffered, at some time by the sample participants, is emotional maltreatment, physical maltreatment and psychological maltreatment. By comparing the means obtained, according to sex, we can conclude that not influence the violence suffered by young couples, which gives it a bidirectional character.